2001
DOI: 10.1071/sr00029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural management on sodosols in northern Tasmania

Abstract: Attributes of 25 Tasmanian sodosols were assessed using field and laboratory techniques to determine changes associated with 4 typical forms of agricultural management [long-term pasture, cropping with shallow tillage using discs and tines, cropping (including potatoes) with more rigorous and deeper tillage including deep ripping and powered implements, and cropping (including potatoes) where the potatoes were harvested when the soil was wet]. Soil organic carbon in the top 150 mm was 2.7% under long-term past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For example, unpublished data by Cotching et al . () found the bulk density in the B21 of 27 Tasmanian Sodosols ranged from 1.02 g cm −3 to 1.72 g cm −3 . Greenwood et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, unpublished data by Cotching et al . () found the bulk density in the B21 of 27 Tasmanian Sodosols ranged from 1.02 g cm −3 to 1.72 g cm −3 . Greenwood et al .…”
Section: Resultsmentioning
confidence: 97%
“…Although Bruand and Gilkes (2002) reported subsoil bulk densities up to 1.91 g cm À3 in a cultivated Sodosol, values for clod density greater than 1.90 g cm À3 are generally higher than values of bulk density reported in the literature for the texture-contrast soils. For example, unpublished data by Cotching et al (2001) found the bulk density in the B21 of 27 Tasmanian Sodosols ranged from 1.02 g cm À3 to 1.72 g cm À3 . Greenwood et al (2006) reported bulk density of a Red Sodosol from northern Victoria ranged from 1.49 to 1.71 g cm À3 whilst clod density ranged from 1.58 to 1.65 at 30-40 cm depth.…”
Section: Effect Of Soil Moisture On Subsoil Porositymentioning
confidence: 99%
“…The soils analysed in this study were pasture and cropped soils previously sampled from farm paddocks in northern Tasmania (latitude 41–42°S, longitude 146–148°E, mean annual temperature 11–12 °C, annual rainfall 600–1000 mm) (Sparrow et al. , 1999; Cotching et al. , 2001, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Further details of the sites, soil sampling and sample preparation are given in Sparrow et al. (1999) and Cotching et al. (2001, 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Estimates of the extent of texture‐contrast soils range from 17.0% (Isbell et al, 1997) to 20% of the Australian landmass (Northcote, 1979; Chittleborough, 1992), including around 80% of agricultural regions in southern Australia (Chittleborough et al, 1994) and approximately 60% of agricultural regions in southwestern Western Australia (Tennant et al, 1992). The texture‐contrast soils are associated with a range of management problems, including waterlogging, poor crop establishment, surface crusting, poor root penetration, desiccation, water repellence, wind erosion, tunnel erosion, salinity, poor nutritional status, hard setting, low infiltration, and poor water holding capacity (Edwards, 1992; Gardner et al, 1992; Tennant et al, 1992; Doyle and Habraken, 1993; Cotching et al, 2001; Hardie et al, 2007; Simeoni et al, 2009). Unlike other soil types, texture‐contrast soils contain an abrupt increase in clay content between the topsoil and the subsoil, which has been widely reported to result in the formation of seasonal perched water tables and subsurface lateral flows (Turner et al, 1987; Gregory et al, 1992; Naidu et al, 1993; Chittleborough et al, 1994; Cox and McFarlane, 1995; Fleming and Cox, 1998; Stevens et al, 1999; Eastham et al, 2000; Cox and Pitman, 2001; Cox et al, 2002; Ticehurst et al, 2003, 2007).…”
Section: Approximate Correlation To International Soil Classificationmentioning
confidence: 99%